PENERAPAN TEORI HUMANISTIK PADA AKTIVITAS MEMBACA DAN BERMAIN ANAK USIA DINI DI TK RAUDHATUL ATHFAL - Sweta Laras Cahyaning Tyas; Nur Hayati (Qalam : Jurnal Ilmu Kependidikan, 2025)
Early childhood education requires an approach that values the uniqueness, needs, and potential of each child. The humanistic theory introduced by Abraham Maslow and Carl Rogers serves as the foundation for child-centered learning, emphasizing unconditional acceptance, empathy, and providing children with space for self-development. This study aims to assess the application of humanistic theory in reading and play activities at TK Raudhatul Athfal Ar Raihan. A descriptive qualitative method was employed through observations and interviews. The research subjects consisted of teachers and children from groups B4 and B5. The findings indicate that teachers applied humanistic principles by giving children the freedom to choose reading materials, express their understanding of stories, and engage creatively in play activities. Teachers also created a safe, warm, and supportive environment, allowing children to explore comfortably. The children showed positive responses, such as increased self-confidence, interaction skills, creativity, and learning motivation. Therefore, the application of humanistic theory through reading and play activities effectively supports child-centered learning and contributes to their holistic development.